Ubiquitin-binding domains in Y-family polymerases regulate translesion synthesis. - Bienko, M; Green, C; Crosetto, N; Rudolf, F; Zapart, G; Coull, B; Kannouche, P; Wider, G; Peter, M; Lehmann, A; Hofmann, K; Dikic, I (2005)
Translesion synthesis (TLS) is the major pathway by which mammalian cells replicate across DNA lesions. Upon DNA damage, ubiquitination of proliferating cell nuclear antigen (PCNA) induces bypass of the lesion by directing the replication machinery into the TLS pathway. Yet, how this modification is recognized and interpreted in the cell remains unclear. Here we describe the identification of two ubiquitin (Ub)-binding domains (UBM and UBZ), which are evolutionarily conserved in all Y-family TLS polymerases (pols). These domains are required for binding of poleta and poliota to ubiquitin, their accumulation in replication factories, and their interaction with monoubiquitinated PCNA. Moreover, the UBZ domain of poleta is essential to efficiently restore a normal response to ultraviolet irradiation in xeroderma pigmentosum variant (XP-V) fibroblasts. Our results indicate that Ub-binding domains of Y-family polymerases play crucial regulatory roles in TLS.